Analisis dan Pemetaan Pemikiran Fikih Moderat di Timur Tengah dan Relasinya dengan Gerakan Fikih Formalis - Abdad, M Zaidi (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
The delopment of thought dichotomically occupies in the level of ahlu al-hadîs dan ahlu ar-ra’yî, though in the contemporary context, those two axis of thoughts have derivated a lot of varieties. Basically, they want to appear as an alternative movement of thought facing the development of modern world. It seems obvious that the issue deals not only with the clash of discourse but also with the clash of politics. In this respect, the phenomenon of mutual blasphemy is manifest among Muslims thinkers. On its peak, each parties use radicalism as a weapon to silence the opponent’s movement. History teaches us, for instance, radicalism movement in Egypt, Algeria, and Turkey carried out by the fundamentalists. This movement eventually comes into world as the movement of moderate Islam, which is more open seeing the problem and more flexible in acquiring the decision through the text. The moderate Islam is open to welcome some current and modern interpretations. Meanwhile the formal Islam is an Islamic group always rigidly understands religious texts in an absolutism way. They tightly select all aspects came from the external entity, and strongly hold the religious texts.